THE EMERGENCE OF NEW SANTRI IN INDONESIA (JOURNAL OF INDONESIAN ISLAM, 2008)
To an extent never seen before, following the collapse of the Soeharto regime in 1998 Islamist groups in Indonesia began to express themselves vocally and explicitly. Islamic discourse has developed apace, ranging from demands that the state lift the ban on the role of Islamic ideology in political parties and mass organizations to accommodate Muslim interests up to calls for the implementation of Islamic shari`ah to replace the so-called secular laws of state. These recent phenomena indicate the emergence of new santris (devout Muslims) differing from their own parents and the older generation in terms of political orientation, religious ideology, and attitude towards inherited traditions. These new types of santri are not only influenced by the local and changing dynamics of Indonesian politics, society and culture but they are also subject to international influences in Islam. Within Indonesia, some of them retain their links with traditionalist or modernist groups, some others keep their distance from them and yet still others show radical orientations. They have become very influential within certain sections of Indonesian society and have gained attention from many observers and researchers.